The Effect of Footwork Trainner on Agility and Vo2max in Badminton Athletes - Bimo, Satrio; Permana, Dhias Fajar Widya (Indonesian Journal of Sport Management, 2024)
This research aims to determine: (1) the effect of footwork trainers on the agility of badminton athletes in the 10-12 year age group at PB Jati Wetan Kudus. (2) the effect of footwork trainer on VO2max of badminton athletes in the 10-12 year age group at PB Jati Wetan Kudus. The research uses an experimental method with a "One Groups Pretest-Posttest Design" design. The population of this study was male badminton athletes aged 10-12 years from PB Jati Wetan Kudus. The agility instrument uses a shuttle run with a validity of 0.87 and a reliability of 0.93. Meanwhile, to measure VO2max, the multistage fitness test (MFT) is used. The population in this study were 10 PB Jati Wetan badminton players. Data collection techniques in this research used documentation and action tests to measure agility and VO2max. The results of this research using SPSS 24 are correlation and paired samples T-test results for agility (r-count = 0.963 and T-test = 8.481) and VO2max (r-count = 0.877 and T-test = -12.667). Training using a footwork trainer has more influence on agility than VO2max. Thus it can be concluded that the footwork trainer can increase the agility and VO2max of badminton players, especially PB Jati Wetan Kudus athletes.